2004
DOI: 10.1098/rstb.2004.1513
|View full text |Cite
|
Sign up to set email alerts
|

A balanced psychology and a full life

Abstract: Psychology since World War II has been largely devoted to repairing weakness and understanding suffering. Towards that end, we have made considerable gains. We have a classification of mental illness that allows international collaboration, and through this collaboration we have developed effective psychotherapeutic or pharmacological treatments for 14 major mental disorders. However, while building a strong science and practice of treating mental illness, we largely forgot about everyday well-being. Is the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(78 citation statements)
references
References 1 publication
2
68
0
8
Order By: Relevance
“…Finally, our study supports advocacy for a combined approach focusing on both individuals' strengths and their deficits, as suggested by leaders in the field of positive psychology. These authors all agree that for optimal human functioning there should be an equal focus on nurturing people's strengths and repairing their weaknesses (Linley, Joseph, Harrington & Wood, 2006;Rust et al, 2009;Seligman, Parks & Steen, 2004). It is not surprising that a combined approach yields better employee results compared to an exclusive focus on POS for strengths use or POS for deficit correction.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our study supports advocacy for a combined approach focusing on both individuals' strengths and their deficits, as suggested by leaders in the field of positive psychology. These authors all agree that for optimal human functioning there should be an equal focus on nurturing people's strengths and repairing their weaknesses (Linley, Joseph, Harrington & Wood, 2006;Rust et al, 2009;Seligman, Parks & Steen, 2004). It is not surprising that a combined approach yields better employee results compared to an exclusive focus on POS for strengths use or POS for deficit correction.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…Therefore, it is plausible that using one's strengths and also remediating one's deficits gives an individual a sense of competence and the feeling that their potential is realised. Therefore, positive psychology should not just concern itself http://www.sajhrm.co.za Open Access with amplifying strengths but also with supporting people in overcoming their weaknesses Seligman et al, 2004).…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…Seligman, Parks and Steen (2004) were first to propose an integrated wellbeing theory termed Authentic Happiness theory, which suggested that the presence of positive emotion, meaning, and engagement were indicative of wellbeing. The dimensions of pleasure and of meaning in Seligman et al's model have been equated with hedonia and eudaimonia respectively.…”
Section: Flourishingmentioning
confidence: 99%
“…Following World Word II, Psychology has concentrated on how to heal wounds with a major emphasis on pathology instead of aiming at helping people flourish (Seligman & Csikszentmihalyi, 2000;Seligman, Parks & Steen, 2004). In a special issue of American Psychologist, Positive Psychology emerges as a new movement.…”
Section: Introductionmentioning
confidence: 99%